Stability of structures : principles and applications - Yoo, Chai Hong.; Lee, Sung Chil, 1957- (Amsterdam ; Boston : Butterworth-Heinemann, 2011)
The current trend of building more streamlined structures has made stability analysis a subject of extreme importance. It is mostly a safety issue because Stability loss could result in an unimaginable catastrophe. Written by two authors with a combined 80 years of professional and academic experience, the objective of Stability of Structures: Principles and Applications is to provide engineers and architects with a firm grasp of the fundamentals and principles that are essential to performing effective stability analysts. Concise and readable, this guide presents stability analysis within the context of elementary nonlinear flexural analysis, providing a strong foundation for incorporating theory into everyday practice. The first chapter introduces the buckling of columns. It begins with the linear elastic theory and proceeds to include the effects of large deformations and inelastic behavior. In Chapter 2 various approximate methods are illustrated along with the fundamentals of energy methods. The chapter concludes by introducing several special topics, some advanced, that are useful in understanding the physical resistance mechanisms and consistent and rigorous mathematical analysis. Chapters 3 and 4 cover buckling of beam-columns. Chapter 5 presents torsion in structures in some detail, which is one of the least well understood subjects in the entire spectrum of structural mechanics. Strictly speaking, torsion itself does not belong to a topic in structural stability, but needs to be covered to some extent for a better understanding of buckling accompanied with torsional behavior. Chapters 6 and 7 consider stability of framed structures in conjunction with torsional behavior of structures. Chapters 8 to 10 consider buckling of plate elements, cylindrical shells, and general shells. Although the book is primarily devoted to analysis, rudimentary design aspects are discussed. The accompanying website will include additional formulas and problems based on the author's on software which is currently being used in corporations. The website will also include equations and examples based on there personal experiences. In addition, the website will include a solutions manual for those who wish to use the book as a text book for a two-semester course. Engineers, Architects, designers, and researcher will find this print/website combination a valuable guide both in terms of its applications of verification of design of structures. Balanced presentation for both theory and practice Well-blended contents covering elementary to advanced topics Detailed presentation of the development Computer programs will be made available through the senior author's web page.
Preface XI -- 1. Buckling of Columns -- 2. Special Topics in Elastic Stability of Columns -- 3. Beam-Columns -- 4. Continuous Beams and Rigid Frames -- 5. Torsion in Structures -- 6. Torsional and Flexural-Torsional Buckling -- 7. Lateral-Torsional Buckling -- 8. Buckling of Plate Elements -- 9. Buckling of Thin Cylindrical Shell Elements -- 10. Buckling of General Shell Elements -- Index.
Includes bibliographical references and index.
Keywords: Structural stability; Safety factor in engineering; TECHNOLOGY & ENGINEERING -- Structural; Safety factor in engineering; Structural stability